Content Moderation As a Political Issue: The Twitter Discourse Around Trump's Ban - Meysam Alizadeh; Fabrizio Gilardi; Emma Hoes; K. Jonathan Klüser; Maël Kubli; Nahema Marchal (Journal of Quantitative Description: Digital Media)
Content moderation — the regulation of the material that users create and disseminate online — is an important activity for all social media platforms. While routine, this practice raises significant questions linked to democratic accountability and civil liberties. Following the decision of many platforms to ban Donald J. Trump in the aftermath of the attack on the U.S. Capitol in January 2021, content moderation has increasingly become a politically contested issue. This paper studies that process with a focus on the public discourse on Twitter. The analysis includes over 9 million tweets and retweets posted by over 3 million unique users between January 2020 and April 2021. First, the salience of content moderation was driven by left-leaning users, and "Section 230" was the most important topic across the ideological spectrum. Second, stance towards Section 230 was relatively volatile and increasingly polarized. These findings highlight relevant elements of the ongoing process of political contestation surrounding this issue, and provide a descriptive foundation to understand the politics of content moderation.